Autonomous Learning English Guide Take Your Phone And Let´S Learn English (2018)
The autonomous learning guide Take Your Phone And Let's Learn English was specifically designed for students to learn English by means of the use of different tools carefully chosen to make the learning process easier for them. The students will find a bunch of units which are going to help them to learn English from the very beginning and reach an A1 level, according to what the CEFR says; This can be possible thanks to the specific selection of topics and units, which iare going to give them through English proficiency by using a big quantity of applications and websites.